The Effect of Wind Velocity on the Suppression of Composite Wing Airfoil NACA 0012 - Kadhem, Hassan Ali; Hussein, Ahmed Abdul (Al-Khwarizmi Engineering Journal, 2019)
The first studies on shocks and vibrations were carried out at the beginning of the 1930s to improve the behavior of buildings during earthquakes. Vibration tests on aircraft were developed from 1940 to verify the resistance of parts and equipments prior to their first use. Flutter is a well-known example of dynamic aero elasticity, where when oscillation of structure interacted with unsteady aerodynamic forces the flutter will occur. Vibration on any structure without damping means that self-harmonic oscillation will occur, and in most cases the oscillation may start to increase until structural failure. This behavior is very similar to resonance phenomena if only the oscillation is being studied as a vibration case. In vibration suppression, the active vibration control is one of the more effective technique which is used for attenuating bad effects of disturbances on structure. In this work, two different composite wings have been used; one of them is made of Glass-fiber random matt and the other is made of woven (0/90 Glass-fiber). The proportional-integral-derivative (PID) control is employed here for studying the suppression of active vibration wing affected by wind velocity flow through wind tunnel in the laboratory of mechanical engineering department at the university of Baghdad. Piezoelectric (PZT (transducers are used as sensors and actuators in vibration control systems. The attack angle was 10 degrees and three different velocities (15, 20, 35 m/s) have been taken to show their effect on the wings vibrations suppression. Is noticed that the suppression of the wing amplitude is reduced when the wind velocity increases for both woven and random composite wing matt. This is happened due to the vortex which has became more violent increase in wind velocity. It is concluded that the composite woven wing has high resistance more than the composite random wing. Also, the maximum control amplitude of woven matt is 1.9 cm and the damping is about 33% at 25 m/s wind velocity while the amplitude is 2.22 cm and the damping is about 53% at 10 m/s wind velocity for random wing.